THE EFFICACY OF TRAMADOL IN THE PREVENTION OF POST SPINAL ANAESTHESIA SHIVERING IN CAESAREAN DELIVERIES - Olawoye OA; Isamade ES; Sanusi AA (Ntec Specialist, 2017)
Background: Shivering associated with subarachnoid block in obstetric patients is a cause of discomfort in this group of patients. Tramadol, a synthetic weak opioid that acts centrally at the mu receptors has been found to be effective in the treatment of shivering after general anaesthesia, but will it be effective in prevention of post spinal shivering also? Objective: The study is aimed at investigating the efficacy of intravenous 1mg/kg tramadol in the prevention of post spinal shivering for Caesarean delivery. Methodology: In a double blinded clinical trial, one hundred (100) healthy obstetric patients who were scheduled for elective or emergency Caesarean section under spinal anaesthesia were randomised into two groups. Immediately after the delivery of the foetus, fifty (50) patients received 1mg/kg tramadol diluted to 2ml with sterile water and fifty (50) patients received 2ml of sterile water. The incidence and intensity of shivering, level of sedation and other complications were recorded. The Statistical Package for Social Sciences (SPSS) version 16 was used for analysis of statistical data. The data was presented as frequencies, proportions and means. The demographic numeric data was compared using Students't' test. The incidence of shivering and side effects was tested by Chi square test. P less than 0.05 was considered as statistically significant. Results: The incidence of shivering was significantly lower in patients who received tramadol than those who received placebo, 18% versus 72% (P less than 0.001). In the placebo group 17 (34%) and 19 (38%) patients had grade one and grade two shivering respectively as compared to 7 patients (14%) with grade one shivering and 2 patients (4%) with grade two shivering in the study group. The severity of shivering was significantly higher in the placebo group (P less than 0.001). There were no significant differences in the sedation scores and other complications, but nausea and vomiting was significantly higher in the study group (P = 0.004 and 0.005 respectively). Conclusion: Intravenous tramadol 1mg/kg is effective in the prevention of shivering following spinal anaesthesia for Caesarean section; however it is associated with nausea and vomiting